Ex vivo C5b-9 Deposition Test to Monitor Complement Activity in Clinical and Subclinical Atypical Hemolytic Uremic Syndrome and in Transplantation-Associated Thrombotic Microangiopathy - Maria Martin; Carmen Llorens-Cebria; Juan León-Román; Janire Perurena-Prieto; Víctor Perez-Beltran; Silvia Saumell; Irina B. Torres; Irene Agraz; Joana Sellarès; Natàlia Ramos; Oriol Bestard; Mercedes López; et al. (Kidney International Reports)
Introduction: Atypical hemolytic uremic syndrome (aHUS) is a complement system (CS)–mediated ultrarare disease that manifests as thrombotic microangiopathy (TMA) with preferential small kidney vessels involvement. Transient CS activation is also observed in secondary TMA or in patients at risk of developing aHUS. There is no gold standard test to monitor disease activity; however, the ex vivo C5b-9 deposition test seems to be a good approach. Methods: We assessed the C5b-9 deposition induced by serum samples of patients with aHUS (n = 8) and with TMA associated with kidney (n = 2), lung (n = 1) or hematopoietic stem cell (HSC) transplantation (HSCT, n = 2) during the acute phase of the disease or in remission. As control for transplant-associated TMA (TA-TMA), we analyzed samples of clinically stable kidney and HSC-transplanted patients without signs of TMA. In addition, we studied 1 child with genetic risk of aHUS during an acute infection. Results: In the acute disease phase or in patients with disease activity despite C5 blockade, a significant increase of C5b-9 deposition was detected. In all patients with clinical response to C5 blockade but one, levels of C5b-9 deposition were within the normal range. Finally, we detected increased C5b-9 deposition levels in an asymptomatic child with genetic risk of aHUS when a concomitant otitis episode was ongoing. Conclusion: The ex vivo C5b-9 deposition test is an auspicious tool to monitor CS activity in aHUS and TA-TMA. In addition, we demonstrate that the test may be useful to detect subclinical increase of CS activity, which expands the spectrum of patients that would benefit from a better CS activity assessment.